DESCRIPTION OF AGGRESSION BEHAVIOR ON STUDENT THAT INVOLVED IN MASS BRAWL AT SMK Y PADANG CITY - Mutia Skunda Ramadani,; Nelia Afriyeni,; Diny Amenike, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Adolescence is a period of transition from children to adulthood. Many of the changes occur as physical and psychological aspect. When adolescent are not able to deal with those changes, they will show negative behavior in theirenvironment. One of the negative behaviors in adolescents that they show is aggressive behavior that can harm others or even themselves. Aggressive behavior is the behavior or behavioral tendencies that had intention to hurt another person either physically or psychologically. One kind of aggressive behavior in adolescents at Padang City is student’s mass brawl. Student’s mass brawl is a mass fights that involve many students. This clash has become a tradition handed down by the student. The aim of this study was to determine the aggressive behavior of student that doing mass brawl. The approach used is descriptive quantitative approach with a basic theory of aggressive behavior by Buss and Perry (1992), which consists of four aspects; verbal aggression, physics aggression, anger and hostility with reliability 0.825. Techniques of data collections are done with the scale of aggressive behavior and open questionnaire about factor that cause themassbrawl. The sampling technique used non-probability sampling with purposive sampling type. Subjects in this study were 109 male student with behavior aggression and involved in mass brawl between schools. The result showed that aggressive behavior in SMK Y included in the low category. While based on the behavioral aspects of aggression was found that the highest aspect is physical aggression followed by anger, verbal aggression and hostility. The highest factor that causes the mass brawl is tradition that handed down from the other students, which this factor is about seniority and doctrine to the junior in the school to revengethem in a fight with their opponent